2015
DOI: 10.1016/j.ijfatigue.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Crack closure and fatigue crack growth near threshold of a metastable austenitic stainless steel

Abstract: In this paper R-ratio effects on fatigue crack growth near threshold region of a metastable austenitic stainless steel (MASS) in two different conditions, i.e. annealed and cold rolled, is investigated. The authors present two approaches to correlate FCGR data for R = 0.1, 0.3, 0.5, 0.7 and K-max = 23 MPa root m using a two-parameters approach (Delta K, K-max and alpha in Kujawski's model) and crack closure model (using Elber's K-op, and in Donald's ACRn2 approaches). The K-op and ACRn2 were experimentally mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Other internal factors affecting the susceptibility to the strain-induced phase transformation are the grain size, their distribution and initial dislocation structure [ 11 , 18 ]. Numerous studies showed that the TRIP effect in the austenitic stainless steel can significantly reduce the fatigue crack growth rate (FCGR) [ 8 , 9 , 19 , 20 ]. Several studies were carried out, in which the austenitic stainless steels were subjected to fatigue crack propagation tests at various temperatures with respect to the martensite-start (M s ) temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other internal factors affecting the susceptibility to the strain-induced phase transformation are the grain size, their distribution and initial dislocation structure [ 11 , 18 ]. Numerous studies showed that the TRIP effect in the austenitic stainless steel can significantly reduce the fatigue crack growth rate (FCGR) [ 8 , 9 , 19 , 20 ]. Several studies were carried out, in which the austenitic stainless steels were subjected to fatigue crack propagation tests at various temperatures with respect to the martensite-start (M s ) temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the light of the TRIP phenomenon, the dissolution of the delta ferrite increases chromium content in the adjacent regions, and together with grain coarsening, can enhance the material susceptibility to the martensitic transformation when externally loaded. Several studies have shown differences in the near threshold FCGR between cold worked and annealed austenitic stainless steels [ 8 , 9 , 19 , 20 ]. However, most of these studies were focused on different aspects of the TRIP and FCGR processes under variable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such residual stress also plays a significant role in affecting the fatigue endurance of surface strengthened materials [42][43][44][45][46][47]. Many literatures [48][49][50][51] have shown that the residual compressive stress resulted from surface mechanical treatment could effectively improve the fatigue resistance. More recently, Zhang et al [52] studied experimentally the fatigue crack-growth behavior in gradient axle steel with residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies of fatigue crack growth in austenitic materials, but mainly due to deformation, with only a few investigating austenitic weld metal [14]. Austenitic filler material is unstable and gets transformed into martensite during fatigue crack propagation due to plastic deformation at the crack tip [15]. During the metastable austenite deformation, two types of martensitic structures can be formed: ε -martensite with hexagonal close packed and α' -martensite, with body centered cubic crystal structure.…”
Section: Introductionmentioning
confidence: 99%